2001
DOI: 10.1053/rvsc.2001.0459
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural pathology of nasal and tracheal mucosa of rabbits experimentally infected with Pasteurella multocida serotype D:1

Abstract: Sixteen 8- to 9-week-old Pasteurella multocida-free New Zealand White rabbits were divided into two equal groups. The first group was inoculated intranasally with P multocida serotype D:1 strain and the second group that was inoculated with phosphate-buffered saline (PBS) only was used as a control group. Pasteurella multocida was isolated from the nasal cavity of all infected rabbits in group 1 and from tracheal swabs of seven rabbits in this group. Four rabbits in group 1 died with clinical signs of septicae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 15 publications
2
12
0
1
Order By: Relevance
“…In the challenge with isolate P-1059 described in this report, we observed a rapid infection phenomenon in which the rabbits were clinically ill within 30 h after intranasal exposure to a low bacterial dose. Similar results have been reported by others using P1059 and other virulent P. multocida isolates in rabbits (1,3,4). These infections might be detectable by PCR or culture because of the high replication rate of the bacteria in the host tissue (35).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the challenge with isolate P-1059 described in this report, we observed a rapid infection phenomenon in which the rabbits were clinically ill within 30 h after intranasal exposure to a low bacterial dose. Similar results have been reported by others using P1059 and other virulent P. multocida isolates in rabbits (1,3,4). These infections might be detectable by PCR or culture because of the high replication rate of the bacteria in the host tissue (35).…”
Section: Discussionsupporting
confidence: 91%
“…Figure 2 illustrates the putative phases of P. multocida respiratory colonization and potential infection of rabbits. Exposure to virulent, invasive strains may result in rapid penetration of the respiratory mucosa, leading to peracute or acute disease (1,3,36,46). In the challenge with isolate P-1059 described in this report, we observed a rapid infection phenomenon in which the rabbits were clinically ill within 30 h after intranasal exposure to a low bacterial dose.…”
Section: Discussionmentioning
confidence: 53%
“…Symptoms of pasteurellosis in most animals range from mild to severe (44, 178,[189][190][191][192][193][194][195][196][197][198]. Mild symptoms include sneezing, copious mucous secretions, mild rhinitis, mild pneumonia with labored breathing, and fever but can progress to disseminated disease (hemorrhagic septicemia [further discussed in "Pasteurellosis and Hemorrhagic Septicemia" below]) and/or atrophic rhinitis (atrophy of nasal mucosa, seromucinous glands, and turbinate bones) associated with toxinogenic strains.…”
Section: Pasteurellosis Pneumonia and Atrophic Rhinitismentioning
confidence: 99%
“…While the original publications on the toxigenic infections or PMT treatment of animals provided no evidence of an inflammatory process, other animal models showed that PMT treatment causes inflammation [63,64]. In addition, our in vitro data using macrophage cell lines or primary bone marrow-derived immune cells show that PMT triggers the production of various pro-inflammatory cytokines [65,66].…”
Section: Pmt As a Potential Carcinogenmentioning
confidence: 87%